Seeing inside the stone - Matthieu Bolay; Filipe Calvão (Revue d'anthropologie des connaissances)
This article puts forth the notion of visual refraction to analyze the subjective and technical construction of grading certificates in the global diamond trade. Research was based on an ethnographic study of rough diamond grading and evaluation courses in gemological laboratories in Belgium and India, as well as interviews with novice and experienced evaluators (Belgium, United States, India, United Kingdom, and Switzerland). By "seeing in the stone" the learning of gestures and procedures meant to bring order to the imperfections of natural objects, we reveal the tensions between the aspirations of objectivity and the subjective visual practices that characterize the classificatory apparatus of the diamond industry. We suggest that the visual expertise learnt by graders consists notably of recognizing and valuing the fallibility of their own sensory assessments. This apparent paradox is constitutive of the certification system and aligns with the rhetoric of exceptionality upon which the diamond industry and its markets are built.